2023
DOI: 10.1021/acsaem.3c00571
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Polymer Segment Species Matters for Electrolyte Properties and Performance in Lithium Metal Batteries

Abstract: Control of homogeneous lithium deposition governs prospects of advanced cell development and practical applications of high-energy-density lithium metal batteries. Polymer electrolytes are thus explored and employed to mitigate the growth of high-surface-area lithium species while enhancing the reversibility of the lithium reservoir upon cell cycling. Herein, an in-depth understanding of the distribution of membrane properties and lithium deposition behavior affected by the selection of polymer segment species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…We performed atomistic MD simulations of the above-mentioned series of polymers using an in-house simulation package with Atomistic Polarizable Potential for Liquid, Electrolytes, and Polymers (APPLE&P) force field. , This force field has been extensively used to investigate liquid and polymer electrolytes and was found to predict properties that are in very good agreement with experiments. ,, Specifically, it was demonstrated that for ether and carbonate-based electrolytes (liquid and polymer) the simulations using the APPLE&P force field predict coordination of Li cation in great agreement with the ab initio MD simulations, accurately capture ion aggregation, clustering, diffusion, and conductivity compared to experiments. In this polarizable force field, each force center has an isotropic polarizability and corresponding induced dipole moments are calculated through a self-consistent approach by minimizing the electrostatic energy of the system. The Thole screening parameter of 0.2 was used to prevent polarization catastrophe.…”
Section: Computational Methodologymentioning
confidence: 97%
“…We performed atomistic MD simulations of the above-mentioned series of polymers using an in-house simulation package with Atomistic Polarizable Potential for Liquid, Electrolytes, and Polymers (APPLE&P) force field. , This force field has been extensively used to investigate liquid and polymer electrolytes and was found to predict properties that are in very good agreement with experiments. ,, Specifically, it was demonstrated that for ether and carbonate-based electrolytes (liquid and polymer) the simulations using the APPLE&P force field predict coordination of Li cation in great agreement with the ab initio MD simulations, accurately capture ion aggregation, clustering, diffusion, and conductivity compared to experiments. In this polarizable force field, each force center has an isotropic polarizability and corresponding induced dipole moments are calculated through a self-consistent approach by minimizing the electrostatic energy of the system. The Thole screening parameter of 0.2 was used to prevent polarization catastrophe.…”
Section: Computational Methodologymentioning
confidence: 97%
“…Atomistic MD simulations were performed using Atomistic Polarizable Potentials for Liquid, Electrolytes, and Polymers (APPLE&P) force fields developed by Wasatch Molecular Incorporated (WMI-MD). It was shown in previous investigations, that the considered force fields accurately predict the behavior of solid polymer electrolytes. A Nosé–Hoover thermostat (frequency of 0.01 fs –1 ) and Anderson–Hoover barostat (frequency of 0.0005 fs –1 ) were exploited to control both temperature and pressure of the system. , Each atomic center was assigned isotropic polarizability, and to avoid polarization catastrophe at short distances, a Thole screening parameter of 0.2 was used. With the SHAKE algorithm (tolerance of 10 –14 ) all chemical bonds were constrained .…”
Section: Methodsmentioning
confidence: 99%
“…The structural compatibility between the primary and secondary segments of the polymer chain plays a significant role. 257 Dissimilarity in molecular electrostatic fields among segments can lead to localized lithium deposition, unstable growth of SEIs and unexpected cell failures during electrochemical operation. 258 Fig.…”
Section: Electrochemical and Chemical Compatibility Of Electrode–sse ...mentioning
confidence: 99%